Elavl1 Impacts Osteogenic Differentiation and mRNA Levels of Genes Involved in ECM Organization - Kota, Satya K.; Lim, Zhu Wei; Kota, Savithri B. (Frontiers in Cell and Developmental Biology, 2021)
Posttranscriptional gene regulation by Adenylate Uridylate (AU) rich element RNA binding protein, Elavl1 has been implicated in embryonic development as well as progenitor cell differentiation. Elavl1 binds to hundreds of cellular messenger RNAs predominantly through interactions with AU-rich elements (AREs) found in the untranslated regions (UTRs) and functions by regulating their stability. Biological functions of Elavl1 during osteogenic differentiation of bone marrow derived mesenchymal stem cells is not well-understood. Here we report that specific knockdown of nuclear localized Elavl1 by RNA interference in multipotent BMSCs led to increased osteogenic differentiation. Differential gene expression analysis following unbiased total RNA sequencing upon Elavl1 depletion during osteogenic differentiation of BMSCs showed increased levels of multiple mRNAs that are involved in extracellular matrix organization. We further show that many of these mRNAs contain Elavl1 binding consensus motifs that are preserved in their 3′ UTRs. RNA stability analyses indicated that depletion of Elavl1 prolongs the steady state RNA levels of several of these mRNAs. Together, our data points to Elavl1 mediated negative regulation of multiple genes involved in ECM organization that play a functional role in MSC osteogenic differentiation.